La infancia como pretexto: autobiografía, etnografía y autoetnografía en Hoyt Street de Mary Helen Ponce. - Bellver Sáez, Pilar (Estudios Ingleses de la Universidad Complutense, 2001)
The Childhood Motive as Pretext: Autobiography, Ethnography and Autoethnography in Hoyt Street by Mary Helen Ponce. Childhood autobiography has traditionally been treated as the nostalgic remembrance of a lost and happy past or as a metafictional reflection on the origins of the writing subject. Chicana writer Mary Helen Ponce’s childhood autobiography Hoyt Street challenges these two models of interpretation by presenting the childhood motive as a pretext to reaffirm and rediscover her Chicano cultural heritage. The first part of the study outlines the debate over the literary value of autobiography. Following Françoise Lionnet concept of autoethnography in her studies of Africa-American and Caribbean female autobiographers, I conclude that Hoyt Street can be better understood as a mixture of literary motives and anthropological commentaries on the formation of a distinctive Chicano urban culture in California during the 50’s. The ethnographic nature of this text can be perceived in the episodic design of the narration, and in the predominance of a third person narrative voice that emphasizes precisely those events in the writer’s life that have cultural significance. On the other hand, the first person narrator uses the childhood motive to poeticize an experience of multiculturalism and to pay tribute to the women of her past who have contributed to her love for writing and literature. The study concludes by establishing the text’s importance witihin contemporary US Latina autobiographical writing as an autobiography that both explains and poeticizes the experience of growing up as a minority in the US. 253 Pilar Bellver Sáez La infancia como pretexto: autobiografía, etnografía y autoetnografía...